Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1104/pp.112.200345
|View full text |Cite
|
Sign up to set email alerts
|

Extending Cassava Root Shelf Life via Reduction of Reactive Oxygen Species Production      

Abstract: One of the major constraints facing the large-scale production of cassava (Manihot esculenta) roots is the rapid postharvest physiological deterioration (PPD) that occurs within 72 h following harvest. One of the earliest recognized biochemical events during the initiation of PPD is a rapid burst of reactive oxygen species (ROS) accumulation. We have investigated the source of this oxidative burst to identify possible strategies to limit its extent and to extend cassava root shelf life. We provide evidence for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
168
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(173 citation statements)
references
References 56 publications
3
168
0
Order By: Relevance
“…Furthermore, other evidence has suggested that overexpression of AOX1 could increase stress tolerance ability by generating less ROS (Vanlerberghe et al, 2009). However, most of these genetics studies were performed on the dicot plants Arabidopsis thaliana and Nicotiana tabacum or on species with unique physiological processes (Wang et al, 2011;Zidenga et al, 2012). Therefore, the function of AOX1 in monocot rice remains largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, other evidence has suggested that overexpression of AOX1 could increase stress tolerance ability by generating less ROS (Vanlerberghe et al, 2009). However, most of these genetics studies were performed on the dicot plants Arabidopsis thaliana and Nicotiana tabacum or on species with unique physiological processes (Wang et al, 2011;Zidenga et al, 2012). Therefore, the function of AOX1 in monocot rice remains largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…PPD is initiated by mechanical damage, which typically occurs during tuberous roots harvesting and progresses from the proximal site of damage to the distal end, making the roots unpalatable within 72 h [22,23]. Reactive oxygen species (ROS) production has been identified as one of the earliest events in PPD [21,22,24]. Under conditions of stress, the equilibrium between the production and scavenging of ROS is disturbed, resulting in a rapid increase in the buildup of ROS known as an oxidative burst [25].…”
Section: Postharvest Physiological Deterioration and Storagementioning
confidence: 99%
“…Based on the stability of each individual contaminant, including its by-products, the mobility can also be spontaneously inluenced by the rate of conversion, thus degradation, and can even become volatilised under suitable conditions [65,70], depending on vapour pressure. Time or length of exposure is a very important aspect, particularly where human exposure is assessed, which is generally neglected or unclear in many recent studies.…”
Section: Behaviour Of Cyanogen and Mycotoxin In Soilmentioning
confidence: 99%